Banks' Foreign Credit Exposures and Borrowers' Rollover Risks Measurement, Evolution and Determinants - Cerutti, Eugenio (Washington, D.C. : International Monetary Fund, 2013)
The recent crises highlighted the role of cross-border banking linkages. This paper proposes two new measures for better capturing creditor banking systems' foreign credit exposures and borrower countries' reliance on foreign bank credit, by combining BIS data with bank-level data. The results indicate that the proposed refinements matter, especially when foreign bank affiliates' funding relies heavily on local deposits. In addition, after developing novel and necessary break-in-series and exchange rate variation adjustments, estimations looking at the driving factors of both measures during 2006-2012 highlight: (i) the role of systemic banking crises and global financial conditions in the evolution of banks' foreign credit exposures; (ii) the role of a larger set of factors in the case of the evolution of borrower countries' reliance on foreign bank credit-how countries borrowed, from whom they borrowed, and global financial and domestic demand conditions.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet